Community Participation and Women’s Empowerment: The Kerala Experience of Participatory Planning and Budgeting (SPRINGER, 2015)
This chapter provides a brief account of Kerala state’s decentralization process and its achievements, particularly in relation to participatory budgeting and women’s empowerment. The chapter describes the process of development as expanding people’s capabilities, and strengthening of local government by devolving functions and finances. With efforts to actively involve people in local governance at every stage, and embed women’s empowerment and poverty reduction in the system, the powers and functions of the grama sabha are actually embedded in the people. Using case studies of women’s empowerment, this chapter highlights the lessons learnt from these reformed structures and processes.